(untitled) - Marx, Karl (New York, 1978)
This book consists of 5 parts. Part 1 presents the writings of the young Marx, the works which have aroused so much interest and caused so much debate in recentyears. Part 2 includes works critical of capitalism. Part 3 deals with the works which outline the program, strategy, and tactics of the revolutionary movement. Part 4 includes writings on society and politics in the nineteenth century, not only European but Asian and Russian as well. The concluding section, part 5, presents the later writings of Engels, in which Marxism was popularized and systematized for the benefit of the masses. The book contains an interpretive general introduction that traces and analyzes the development of Marxist philosophy; head-notes to each selection; a full chronology of major events in the lives of Marx and Engels; a note on texts and terminology and an index
Keywords: communism,socialism; collected works,collected works